TINJAUAN FISIOLOGIS DOMESTIKASI ULAT SUTERA LIAR Attacus atlas (Lepidoptera: Saturniidae) - Damiana Rita Ekastuti (Research Center for Biology-Indonesian Institute of Sciences, 2012)
Attacus atlas are insects producing silk materials having high economic value. It lives from South East Asia, almost all Indonesia until Australia.The demand of silk from Attacus atlas is quite high (10 tons/month). The A. atlas silk is very exclusive, with permanent in variety colors from light to dark brown. At present, to response the high demand, the people get cocoons from nature. This action could reduce result, and the scarcity of the insect. Beside that, rearing was done by placing the larvae on the trees (outdoor rearing). The outdoor rearing resulted in high mortality because of predators or stress. Better rearing is conducted by indoor rearing, that resulted in high survival rate, and high cocoon or egg production. It is because indoor rearing was supported in better environmental condition than outdoor condition that support physiological process eficiently.